Interaction between Humans as an Implementation of Hablumminannas in Realizing Tolerance Between Communities of the Same Religion and Other Religions - Didik Himmawan; Annisatul Muthi’ah; Safitri Ramahdani (Annujum: Journal of Humaniora and Law, 2025)
Every religion teaches the values ​​of humanity and an attitude of tolerance towards fellow human beings. Humanity is an important characteristic for humans that must be maintained, because humans essentially have good intellectual and moral qualities called humanity. The purpose of this study is to determine the Interaction between Humans as an Implementation of Hablumminannas in Realizing Tolerance Between Communities of the Same Religion and Religion. The research method used in this study is a qualitative method with a literature study in the technique of reviewing and concluding various relevant literature sources. The results of this study are that the interaction between humans, both in the context of the relationship with Allah (habluminallah) and the relationship between fellow human beings (habluminannas), has an important role in building social harmony. Tolerance, both between people of the same religion and between people of different religions, is the key to maintaining harmony and peace in society.